The notorious Scarlett and Browne - Stroud, Jonathan (Alfred A. Knopf, 2023)
Outlaws Scarlett McCain and Albert Browne have managed to outwit their pursuers and escape into Mercia and Northumbria, but old enemies from Scarlett's past and a sinister new threat from Albert's world puts their friends in a dangerous situation. Forced to pull off an impossible job to save their friends, Scarlett and Albert find themselves unsure of who they can trust and how far they are willing to go to do so.